2009
DOI: 10.1073/pnas.0810300106
|View full text |Cite
|
Sign up to set email alerts
|

The grinding tip of the sea urchin tooth exhibits exquisite control over calcite crystal orientation and Mg distribution

Abstract: The sea urchin tooth is a remarkable grinding tool. Even though the tooth is composed almost entirely of calcite, it is used to grind holes into a rocky substrate itself often composed of calcite. Here, we use 3 complementary high-resolution tools to probe aspects of the structure of the grinding tip: X-ray photoelectron emission spectromicroscopy (X-PEEM), X-ray microdiffraction, and NanoSIMS. We confirm that the needles and plates are aligned and show here that even the high Mg polycrystalline matrix constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(167 citation statements)
references
References 27 publications
7
160
0
Order By: Relevance
“…Both experimental and computational investigations in the literature provided evidence indicating that calcite crystals with low concentrations of Mg are stable in structure (19,(69)(70)(71); these studies, however, predicted that high concentrations of Mg (≥ ∼50 atom %) may prevent crystal formation because of the increasing structural stiffness and distortion resulting from the random Mg substitution of Ca (72,73). Recent studies (73) using computational methods reported that substituting Ca by Mg in calcite crystals can alter the cation-C and the cation-cation interatomic distances significantly and cause local tilt of the CO 3 2− groups while maintaining the C-O (within the CO 3 2− ) and the cation-O bond lengths constant.…”
Section: Resultsmentioning
confidence: 99%
“…Both experimental and computational investigations in the literature provided evidence indicating that calcite crystals with low concentrations of Mg are stable in structure (19,(69)(70)(71); these studies, however, predicted that high concentrations of Mg (≥ ∼50 atom %) may prevent crystal formation because of the increasing structural stiffness and distortion resulting from the random Mg substitution of Ca (72,73). Recent studies (73) using computational methods reported that substituting Ca by Mg in calcite crystals can alter the cation-C and the cation-cation interatomic distances significantly and cause local tilt of the CO 3 2− groups while maintaining the C-O (within the CO 3 2− ) and the cation-O bond lengths constant.…”
Section: Resultsmentioning
confidence: 99%
“…These teeth, despite being composed primarily of calcite, are able to grind through rocks of a similar composition [174][175][176]. This is achieved by highly aligned and continuous growth of Mg-reinforced calcite that results in self-sharpening grinding tips [174,176].…”
Section: Sea Urchin Spinesmentioning
confidence: 99%
“…8 All echinoderms align the calcite crystals of their mineralized structures in a highly cooriented fashion, 10 making this interesting physical aspect a shared trait, a synapomorphy, of this phylum. 11 Recently, Ma et al 12 reported that the teeth from the species Paracentrotus liVidus have two highly cooriented crystalline blocks oriented differently by a few degrees and that these crystalline blocks interdigitate near the grinding tip. They also reported that the calcite of all components in each block, the plates, the fibers, and the polycrystalline matrix, is highly cooriented from the nanometer to the centimeter scale.…”
Section: Introductionmentioning
confidence: 99%